Peran Komunitas Masyarakat Dalam Mewujudkan Kemandirian Desa Sukamulya Kecamatan Baregbeg Kabupaten Ciamis - Dea Nurgiawan; Dini Yuliani; Otong Husni Taufiq; Regi Refian Garis (Papsel Journal of Humanities and Policy, 2024)
This research is motivated by the author's curiosity about how the role of the community in realising village independence. The purpose of this research is to find out the role of the community in realising village independence. The method used in this research is qualitative research method with descriptive type. The data collection techniques in this research are observation, interview, and documentation. The data analysis technique used is interactive analysis consisting of three flows, namely: data reduction, data presentation, and conclusion drawing. Data validity checking is done by triangulation. Triangulation is the process of finding conclusions by rechecking from various angles. Based on the results of the research and discussion that: 1) The role of the community in realising the independence of Sukamulya Village, Baregbeg Sub-district, Ciamis Regency has not fully run optimally. 2) The obstacles faced by the community in realising the independence of Sukamulya Village, Baregbeg District, Ciamis Regency are lack of information and confirmation and lack of understanding and the same agreement 3) The efforts made in overcoming these obstacles are carried out by dialogue and deliberation and providing input to the village government so that information can reach the community. Keywords: Community, Village Government, Village Independence